New record of Sphaenorhyncus prasinus Bokermann, 1973 (Anura, Hylidae) from northeastern Brazil - Washington Luiz Silva Vieira; Kleber Silva Vieira; Fagner Ribeiro Delfim; Frederico Gustavo Rodrigues França; Rômulo Romeu Nóbrega Alves; Paulo Fernando Guedes Pereira Montenegro; Gentil Alves Pereira Filho (Check List)
The distribution of Sphaenorhynchus prasinus Bokermann, 1973 in Brazil extends from eastern Bahia to eastern and central Minas Gerais, northern Espírito Santo, with isolated records in Alagoas and Pernambuco. Here, we present a new record of the occurrence of S. prasinus and the potential distribution of the species throughout the Brazilian Atlantic Forest. Our record increases the distribution of the species by 944 km from the type locality in the municipality of Ilhéus, state of Bahia and by 80 km from the northernmost record in Igarassu, Pernambuco.